Managing Knowledge in FIT Academic Environment : A Proposed Knowledge Sharing Framework - Asma Hanee, Ariffin (2004)
In this knowledge-based era, the successful of an organization, espescially in academic field, is not completely depending on technical supports and budgets but also the sytematic flow of managing the knowledge and sharing this assets among the staff. As knowledge management includes knowledge distribution and sharing, this study focused on how academic staff in Faculty of Information Technology (FIT) can capture, increase and share their knowledge towards enhancement in teaching and research activities. Based on the mixture of Socialization, Externalization, Combinaton and Internalization (SECI) process, studies from other universities and interviews among FIT lecturers, this study proposed a knowledge sharing framework; Tacit and Explicit Approaches Framework (TEA Framework), to enhance current knowledge sharing activities in this academic environment. It is hoped that this framework will assist in developing an effectiveness knowledge management system (KMS), in future.